Band-gap-confinement and image-state-recapture effects in the survival of anions scattered from metal surfaces - Schmitz, Andrew; Shaw, John; Chakraborty, Himadri S.; Thumm, Uwe (My University, 2010)
The resonant charge transfer process in the collision of hydrogen anions with metal surfaces is described within a single-active-electron wave-packet propagation method. The ion-survival probability is found to be strongly enhanced at two different surface-specific perpendicular velocities of the ion. It is shown that, while the low-velocity enhancement is induced from a dynamical confinement of the ion level inside the band gap, the high-velocity enhancement is due to electron recapture from transiently populated image states. Results are presented for Li(110), Cu(111), and Pd(111) surfaces.